Cherax acherontis (Decapoda: Parastacidae), the first cave crayfish from the Southern Hemisphere (Papua Province, Indonesia) - Patoka, Jiří; Bláha, Martin; Kouba, Antonín (Zootaxa, 2017)
Cherax acherontis n. sp., is a crayﬁsh endemic to the submerged river Yumugima in Hagepma/Jugurama cave in the New Guinea Highlands, Jayawijaya Regency, Papua Province, Indonesia. This species is the first cave crayfish from the Southern Hemisphere. The new species is most similar to Cherax monticola. Both species can be easily distinguished by certain morphological characteristics, which easily demonstrate C. acherontis n. sp. is a valid species.
Keywords: severní raci; Animals; Papua New Guinea; New Guinea; Indonésie; Papua Nová Guinea; Nová Guinea; Caves; Indonesia; Astacoidea; zvířata; jeskyně